Peranan Desa Adat Intaran Dalam Pengelolaan Pantai Mertasari Kecamatan Denpasar Selatan - Ni Putu Ayu Anistya Dewi; I Putu Anom (JURNAL DESTINASI PARIWISATA, 2017)
Bali is one of the tourist destinations that is growing rapidly in Indonesia. Most people when they hear about bali island are synonymous with exotics beach. Bali is famous with the beautiful beach panorama. One of tourist attraction in the Bali Island is Mertasari Beach. Mertasari beach is an indigenous Intaran village. In tourism management is done one way to approach community institutions, namely the indigenous village institutions. Intaran village is one of the indigenous villages that located in South Denpasar District. In terms of management in Mertasari Beach, Intaran village started to build a management in December 2014 by forming BUMDES (Owned Indigenous Village). However, management Mertasari Coast has not fully given to the village. In conducting the study authors used data collecting observation, interviews, documentation studies and literature studies with similar previous studies. These results indicate that the role of Indigenous Village in Beach Intaran in the management of Mertasari terms of existing management stage such as: Planning (Planning) covers, community empowerment programs, increase sustain ability in Mertasari Beach, improve hygiene in Mertasari Beach and financial planning. Organizing (Organizing) includes, forming management organizational structure is accompanied by a clear task. Mobilization of people (Actuating) include, mobilize communities in managing Mertasari Beach, and Supervision (Controlling) include, supervision in the field of employment, supervision in the field of security and supervision of the trader. Keywords: Management, Role, Indigenous Village